CTIM-04. BIOMARKER IMMUNE CORRELATES IN NEWLY DIAGNOSED GLIOBLASTOMA (GBM) TREATED WITH ATEZOLIZUMAB IN COMBINATION WITH TEMOZOLOMIDE (TMZ) AND RADIATION. (12th November 2021) - Weathers, Shiao-Pei; Knafl, Mark; Parra, Edwin; Hernandez, Sharia; Solis, Luisa; Espiridion, Beatriz Sanchez; Wistuba, Ignacio; Futreal, Andrew; Maru, Dipen; Kamiya-Matsuoka, Carlos; Harrison, Rebecca; Joseph, Victory; et al.
Abstract: BACKGROUND: Checkpoint inhibitor therapy has demonstrated overall limited efficacy in the treatment of GBM. Mechanisms of resistance to checkpoint blockade need to be better elucidated. Analysis of the tumor microenvironment is critical to identify correlates of response to immune checkpoint blockade. 60 newly diagnosed GBM patients unselected for MGMT status underwent treatment with concurrent atezolizumab with radiation therapy and TMZ followed by adjuvant atezolizumab and TMZ (NCT03174197). Clinical data has been reported previously. METHODS: Tissue image immunoprofiling was conducted using 2 multiplex immunofluorescence (mIF) panels against; CD3, CD8, PD-1, PD-L1, Granzyme B, FOXP3, CD45RO, CD68, and GFAP antibodies. PDL-1 (Clone SP263) malignant cells expression was assessed by immunohistochemistry. Correlations between mIF biomarkers co-expressions, IHC PD-L1, and clinical outcome including OS, radiographic response, and PFS were evaluated. RESULTS: Of 60 patients enrolled, image immunoprofiling was performed successfully on pre-treatment tissue in 48 patients. 20 of 60 patients underwent re-resection for suspected recurrent disease of which 10 patients had immunoprofiling performed successfully on pre and post treatment samples. An analysis of CD3CD8+ cytotoxic T lymphocytes was consistent with prior work, showing no or relatively low levels at baseline, and no association with clinical outcome. PDL-1 expression by IHC, at thresholds of >1% or >5%, was not associated with clinical outcome. Tumors with a higher number of GFAP-expressing cancer cells had a significantly lower tumor response (p< 0.05) and median OS (430 vs. 799 days, p< 0.01). CONCLUSIONS: For newly diagnosed GBM patients treated with standard of care radiation and temozolomide in combination with atezolizumab, T-cell levels and PDL-1 expression were not predictive of outcome. GFAP may represent a novel predictive biomarker of overall survival. Ongoing studies to evaluate the gut microbiome and tumor genomic (WES, CNA) and transcriptomic (RNAseq) features of these and matched tumors are underway.